The correlation of circulating miR-29b and inflammatory markers with albuminuria in hypertensive patients - Cheng Huang; Yu-Qing Huang (Clinical and Experimental Hypertension, 2020)
Aims Circulating miR-29b and inflammatory process play a vital role in hypertension and hypertensive nephropathy. The aim of the present study was to investigate the association of circulating miR-29b and inflammatory markers with albuminuria and assess the predictive value of circulating miR-29b for albuminuria in essential hypertension. Methods This cross-sectional study was continuously enrolled 150 subjects and were divided into three groups based on random urinary albumin/creatinine ratio (UACR, mg/g), the patients with ACR<30 mg/g were classified as normal albuminuria, the values of 30< ACR<300 was defined as micro-albuminuria while the group with ACR over 300 mg/g are macro-albuminuria. Circulating miR-29b was assessed by quantitative real-time polymerase chain reaction (qRT-PCR). Multivariate logistic regression and area under the ROC curve (AUC) were used. Results We found miR-29b, C-reactive protein, and transforming growth factor-β1 (TGF-β1) in macro-albuminuria group were significantly higher than those in the micro-albuminuria and normal albuminuria group. The level of miR-29b was positively associated with TGF-β1, C-reactive protein, and UACR, while negatively related to glomerular filtration rate. Circulating miR-29b was a significant independent determinant factor for albuminuria. Conclusion Our results provided a clinical evidence of a positive association between circulating miR-29b, inflammatory markers, and UACR, and implied miR-29b was a significant independent determinant factor for albuminuria.